ЗБРОЯ, ЯК ІСТОРИЧНЕ ДЖЕРЕЛО ДО ВИВЧЕННЯ ІСТОРІЇ УКРАЇНИ XVI-XVII СТ. (НА МАТЕРІАЛАХ ЦДІАУ м. ЛЬВІВ) (Zaporizhzhia Historical Review, 2021)
And to the article is demonstrated, that the weapon is by a valuable historical source for the Ukrainian history XVI-XVII centuries. On an example city of L’viv, is studied a complex situation of many-sided nature of the analysis of weapon for research of the Ukrainian history